2019
DOI: 10.3897/zookeys.819.29447
|View full text |Cite
|
Sign up to set email alerts
|

Myriapoda of Canada

Abstract: The currently documented fauna of described species of myriapods in Canada includes 54 Chilopoda, 66 Diplopoda, 23 Pauropoda, and two Symphyla, representing increases of 24, 23, 23, and one species, respectively, since 1979. Of the 145 myriapod species currently documented, 40 species are not native to Canada. The myriapods have not been well documented with DNA barcodes and no barcodes are available for Pauropoda. It is conservatively estimated that at least 93 additional myriapods species will be discovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…However, predator behavior has been documented in the Symphylella genera, and it is believed that predatory habits are more widespread within the Scolopendrellidae family [215]. Individuals of Scutigerellidae are phytophagous feeding on roots (fine roots and root hairs) and other plant material [215] and can damage plants if the population density is high [7,216].…”
Section: Myriapoda Symphylamentioning
confidence: 99%
“…However, predator behavior has been documented in the Symphylella genera, and it is believed that predatory habits are more widespread within the Scolopendrellidae family [215]. Individuals of Scutigerellidae are phytophagous feeding on roots (fine roots and root hairs) and other plant material [215] and can damage plants if the population density is high [7,216].…”
Section: Myriapoda Symphylamentioning
confidence: 99%
“…Many non-native terrestrial arthropod species have been introduced to Canada since the time of European colonization, most of them inadvertently and some intentionally, e.g., for biocontrol (Langor et al 2009). The authors of most Biota of Canada papers considered and reported on the proportion of the fauna that is non-native.…”
Section: Non-native Speciesmentioning
confidence: 99%
“…Small glacial refugia that existed in Beringia and on offshore islands (Roberts and Hamann 2015), in the Cypress Hills of Alberta and Saskatchewan (Pielou 1991), and possibly in what is now northern British Columbia (Marr et al 2008), contained some species that persisted during glaciation, but the vast majority of the species now living on land and in freshwater in Canada recolonized the area from the un-glaciated south (Matthews 1979). In addition, thousands of non-native species, mainly from Europe and Asia, were later unintentionally or intentionally introduced to North America subsequent to European colonization and are now established in Canada (e.g., Langor et al 2009, Klimaszewski et al 2010D Langor unpubl. data).…”
Section: Introductionmentioning
confidence: 99%
“…Not many people have studied the systematics of centipedes in North America, and practically no modern systematics work on the group has occurred in Canada (Langor et al. 2019). The most prolific centipede taxonomists in North America were Ralph V. Chamberlin (more than 120 publications from 1901 to 1966), Ralph E. Crabill, Jr. (more than 62 publications from 1949 to 1981), and Rowland M. Shelley (more than 20 publications from 1978 to 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For almost a century thereafter, only occasional centipede records from Canada appeared in the literature, mostly reported by Chamberlin and Crabill, and the Chilopoda largely escaped the attention of Canadian scientists (Langor et al. 2019). The most notable contribution was a treatment of the Chilopoda of Newfoundland and Labrador (Palmén 1954), based on collections made during the Fennoscandian expeditions of 1949 and 1951; this remains the only Canadian jurisdiction to receive such a comprehensive faunal treatment.…”
Section: Introductionmentioning
confidence: 99%